Higher body weight and distant metastasis are associated with higher radiation exposure to the household environment from patients with thyroid cancer after radioactive iodine therapy. Issue 35 (September 2017) - Kuo, Sheng-Fong; Ho, Tsung-Ying; Liou, Miaw-Jene; Lin, Kun-Ju; Cheng, Ru-Chin; Chan, Sheng-Chieh; Huang, Bie-Yui; Ng, Soh-Ching; Liu, Feng-Hsuan; Chang, Hung-Yu; Hsieh, Sheng-Hwu; Chiang, Kun-Chun; et al.
Abstract : Abstract: There were insufficient data regarding radiation exposure to the household environment from patients with thyroid cancer who received radioactive iodine (RAI) therapy in Asia; we therefore performed the present study at the Chang Gung Memorial Hospital in Keelung, Taiwan. Patients with papillary or follicular thyroid cancer who received 3.7 GBq (100 mCi) RAI were enrolled in this prospective hospital-based study. The enrolled patients were asked to place a thermoluminescent dosimeter in the living room, bedroom, and bathroom of their houses for 4 weeks to measure radiation exposure to the household environment. A total of 43 patients (18 men and 25 women; mean age 51 ± 13 years) who received 3.7 GBq (100 mCi) RAI completed the study. The mean value of total radiation exposure over 4 weeks from the patients to the bedroom, bathroom, and living room (eliminating the background radiation factor) was 0.446 ± 0.304 (0.088–1.382) mSv. We divided the patients into 2 groups: those with more than and less than the mean value of total radiation exposure to the bedroom, bathroom, and living room. Factors associated with the higher amount of radiation exposure from the patients to the household environment were patient body weight ( P = .025, univariate analysis; P = .037, multivariate analysis, odds ratio [95% confidence interval] 1.067 [1.004–1.134]) and distant metastases based on 131 I post-therapy scanning ( P = .041, univariate analysis; P = .058, multivariate analysis, odds ratio [95% confidence interval] 6.453 [0.938–44.369]); age, sex, body mass index, renal function, serum stimulated thyroglobulin level, and recombinant human thyroid-stimulating hormone use were not associated with the amount of radiation exposure from the patients to the household environment. Higher body weight and distant metastases may be the best predictors for higher radiation exposure to the household environment from patients with thyroid cancer after RAI therapy.